The effect of comorbid substance use disorders on treatment outcome for anxiety disorders - McEvoy, Peter; Shand, F. (Pergamon, 2008)
This study examined the impact of concurrent substance use disorders (SUDs) on outcomes for psychotherapy targeting anxiety disorders. Study 1 (N = 484) sought to determine the prevalence of SUDs in a sample referred to a community anxiety disorders clinic, as well as the impact of comorbid SUDs on outcomes for a subsample (n = 200) completing cognitive behavior therapy (CBT). Around one-quarter (22–29%) of patients with one or two anxiety disorders met criteria for at least one SUD, but this rate was substantially higher (46%) for patients with three anxiety disorders. Concurrent SUDs were associated with higher levels of anxiety but not depression or stress, compared to those without a SUD. However, concurrent SUDs did not moderate treatment outcomes. Study 2 (N = 103) focused on the impact of alcohol use on diagnosis-specific symptom measures and generic measures of distress and disability, following a course of CBT for panic disorder or social phobia. Pre-treatment alcohol use did not predict changes in panic symptoms, performance anxiety, distress, or disability, but it did predict changes in social interaction anxiety. Problem drinking per se did not have any predictive utility in terms of treatment outcome. These findings suggest that clinicians treating patients for a primary anxiety disorder and concurrent SUD can be relatively optimistic about treatment outcomes.